PKM virtual: Model dan strategi gerakan sosial pandemi Covid 19 masyarakat Jatimulyo Kabupaten Tulungagung - Ubaidillah, Ubaidillah; Nisai, Ariski Titis Ainun; Sapitri, Neli Ana (Nur Science Institute, 2021)
The COVID-19 pandemic that has hit Indonesia for approximately 2 years has had an impact on the community's economy, education, and religion. The purpose of this research is to help food consumption security for people affected by the COVID-19 pandemic. The method used in this research is virtual service by using the social assistance and social services approach virtually. The results of this study are the first to distribute aid in the form of food to people affected by the COVID-19 pandemic, especially to the elderly. As well as social services in the form of spraying disinfectants in the community through the head of the RT, distributing masks and hand sanitizers to the community as an effort to prevent the transmission of COVID-19. Second, efforts to create a healthy environment as an effort to minimize the transmission of COVID-19. Third, many people still think that the transmission of COVID-19 can be avoided simply by staying away from infected people, even though this virus can be transmitted through particles attached to objects around us, sneezing, and coughing.